PENINGKATAN KOMPETENSI PEDAGOGICAL CONTENT KNOWLEDGE BAGI GURU SMP DAN SMA DI KECAMATAN TEHORU - Tamalene, Hanisa; Laamena, Christina M; Rumalean, M Samad; Talib, Taufan (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Apart from teaching and research in tertiary institutions, Community Service (PKM) is also an essential element in the tri dharma of higher education that every lecturer must carry out. Teaching is a complex process; teaching is not just about conveying information to students but includes many actions that must be taken. In the community service activity that will be carried out with the title Improving Pedagogical Content Knowledge (PCK) for middle and high school teachers, it aims to provide information to teachers about the use of Pedagogical Content Knowledge (PCK) competencies in learning to improve teachers' understanding of these competencies further. This activity also helps improve the quality of teaching and student learning that supports in-depth discussions with colleagues, builds camaraderie, creates a reflective and sustainable learning culture, and provides opportunities for teachers to learn curriculum, management, content, and pedagogy. The method used in this service activity is to provide information, materials, and examples about the competence of Pedagogical Content Knowledge (PCK) and Technology Pedagogical Content Knowledge (TPACK). To increase the knowledge and skills of the relevant participating teachers (PCK) and Technology Pedagogical Content Knowledge (TPACK) and further explore the unique mix of content and pedagogy from the teacher, which will ultimately form a professional understanding of the teacher himself